THE URGENCY OF SOCIAL INSTITUTIONS IN EDUCATION - Muhammad Nur Hadi (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
Social institution is a system of behaviour and relationships that are cantered on activities to meet the complexity of needs in people's lives that emphasize systems of behaviour or norms to meet needs. social institution in human life is an association or unit of human beings who live together. Social institution is where there is an organizational structure and a factor, which is shared by members of the group so that the relationship between them grows closer. In order to win the competition, every society must master various fields of science, technology (science and technology) and the professional skills and expertise needed to spur the added value of various industrial sectors and economic equality in a sustainable manner. The very strong emphasis on human resource development, as mandated by the 1945 Constitution, namely education is oriented towards efforts to educate the nation's life, shows that the Indonesian nation has a very large commitment to catching up with other nations in the world.